2018
DOI: 10.1007/s13337-018-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of viruses through thermotherapy and meristem culture in apple cultivar ‘Oregon Spur-II’

Abstract: In the present study, an attempt was made to eliminate apple chlorotic leaf spot virus, apple mosaic virus, apple stem grooving virus and apple stem pitting virus from apple cultivar 'Oregon Spur-II'. Thermotherapy was carried out at 37-40 °C for 4 weeks followed by culturing of meristems of different sizes. During establishment of explants, highest survival percentage (62.35%) and proliferation (30.68%) was recorded during summer season. However, size of meristems and position of buds from where meristems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In vitro culture is a successful method to eradicate apple viruses and detailed information on this subject before the twenty-first century can be found in several comprehensive reviews (Laimer and Barba 2011;Panattoni et al 2013;Barba et al 2015). Advances on this subject since 2000 reported improvements of in vitro-based methods for apple virus eradication, including thermotherapy (Paprštein et al 2008;Hu et al 2015bHu et al , 2017Vivek and Modgil 2018;Wang et al 2018b), chemotherapy (James et al 1997;Paprštein et al 2013;Hu et al 2015b), combining chemotherapy with thermotherapy (Hu et al 2015b), shoot tip culture from adventitious buds (Wang et al 2016), cryotherapy (Li et al 2016;Romadanova et al 2016a;Bettoni et al 2018) and combining thermotherapy with cryotherapy (Zhao et al 2018) (Fig. 5).…”
Section: Virus Eradicationmentioning
confidence: 99%
“…In vitro culture is a successful method to eradicate apple viruses and detailed information on this subject before the twenty-first century can be found in several comprehensive reviews (Laimer and Barba 2011;Panattoni et al 2013;Barba et al 2015). Advances on this subject since 2000 reported improvements of in vitro-based methods for apple virus eradication, including thermotherapy (Paprštein et al 2008;Hu et al 2015bHu et al , 2017Vivek and Modgil 2018;Wang et al 2018b), chemotherapy (James et al 1997;Paprštein et al 2013;Hu et al 2015b), combining chemotherapy with thermotherapy (Hu et al 2015b), shoot tip culture from adventitious buds (Wang et al 2016), cryotherapy (Li et al 2016;Romadanova et al 2016a;Bettoni et al 2018) and combining thermotherapy with cryotherapy (Zhao et al 2018) (Fig. 5).…”
Section: Virus Eradicationmentioning
confidence: 99%
“…So far, ASGV has been successfully eradicated from infected apple and pear plants by thermotherapy‐based methods such as thermotherapy followed by shoot tip culture (Hu et al ., ; Vivek & Modgil, ; Wang et al ., ), chemotherapy followed by thermotherapy (Hu et al ., , ; Wang et al ., ), thermotherapy followed by shoot tip grafting (Hu et al ., , ; Wang et al ., ) and thermotherapy followed by shoot tip cryotherapy (Wang et al ., ; Zhao et al ., ). Contrary to these findings, Paprstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, virus eradication by exogenous application of melatonin does not require extra facilities and can be conducted in any tissue culture laboratory, whereas ASGV eradication by thermotherapy and cryotherapy requires expensive growth chambers in the former, and cryogenic procedures which may not be available in some laboratories in the latter. Thirdly, ASGV eradication frequencies obtained in the present study (95%) were comparable with those reported in previous studies (Hu et al ., , ; Vivek & Modgil, ; Zhao et al ., ). Furthermore, 100% survival and 85% shoot regrowth levels of the shoot tips were obtained in the present study, which were higher than 62.5% (Paprstein et al ., ) and 62.4% (Vivek & Modgil, ) of shoot tip survival levels in thermotherapy followed by shoot tip culture, 65% of shoot tip survival when combining thermotherapy with chemotherapy (Hu et al ., ), 63.0% of shoot tip grafting success in thermotherapy followed by shoot tip grafting (Hu et al ., ) and 33–76% of shoot regrowth levels in thermotherapy followed by cryotherapy (Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations